Determination of significant factors for sugarcane fiber extraction as potential dielectric composite material - Norazwina, Zainol; Mohamad Eizlan, Mohammad Radzi; Nor Hazwani, Aziz (Springer Nature, 2024)
This study aims to determine the significant factors involved in the extraction of sugarcane fiber as a potential dielectric composite material. The factors include sugarcane waste weight (0.5 and 2.5 g), ratio of sugarcane waste to distilled water (1:15 and 1:20), boiling time (30 and 50 min), and cutting length (5 and 10 cm). The factors were analyzed using the Design-Expert software through a two-level factorial analysis to determine the significant factor. The extracted fiber was analyzed for cellulose content using a Kurschner-Hanack method, and the permittivity value was determined through an Agilent vector network analyzer (VNA). The results show that the ratio of sugarcane waste to distilled water and boiling time were the two most significant factors contributing to the cellulose content and permittivity value of the extracted fiber. The best conditions for sugarcane extraction were obtained at 2.5 g sugarcane waste, 1:20 ratio of sugarcane waste to distilled water, 50 min boiling time, and cutting length of 10 cm, resulting in 47.25% cellulose and 3.12 permittivity value. The findings of this study suggest that sugarcane waste could be a potent material for dielectric composite with a suitable application as a microwave absorber.